DEFINITION OF DUCTUS VENOSUSFLOW - A WAY TO IMPROVE OF THE ANTENATAL DIAGNOSIS OF FETAL DISTRESS - Васильєва, І.А. (World of Medicine and Biology, 2015)
We areusing the Doppler in the umbilical artery for evaluation of the fetal condition in the uterus during the second and third trimesters of pregnancycurrently, but the indicators of venous blood flow in the fetus not taken into account. Blood with a high oxygen contentlocalized in the fetal venous system, namely in the umbilical vein andductus venous, therefore, the study of venous hemodynamics may be additional pathogenetic criteria for evaluating the fetal hypoxia. The data of the research, in particular TRUFFEL, hasshown the effectiveness of the use of venous hemodynamics in the ductus venosusas indicators for the correct diagnosis of antenatal fetal distress. Objective - to develop of auxiliary noninvasivecriteriaof antenatal fetal distress that will predict the severity of the fetus status and the time limit his life in a distress. Methods.We conducted a retrospective analysis of 56 cases of fetal death in the period from 26 to 39 weeks. The pregnant women had had inpatient treatment. We used Doppler and ultrasound to diagnose the fetal condition. The study includes: investigated of the blood flow in the umbilical artery and ductus venosus, defined of the fetal biometric size and calculated of the amniotic index. Results.The pregnant women were divided into two clinical groups for gestational term of antenatal fetal distress andantenatal death.The first group - 18 cases (32.14%) when fetal distress was diagnosed in the period 26-32 weeks, while the follow-up after diagnosis distress to antenatal fetal death ranged from 3 days to 5 weeks (19 ± 6,59 days).The second group - at 32-39 weeks of gestation: in the 38 cases in the second group (67.87%) of long-term observation of antenatal fetal distress was not, because after diagnosis of fetal distress as zero and reverse flow in the umbilical artery, for pregnant women had been proposed active tactics - immediate delivery.Antenatal fetal death occurred to theestablished practices criteria of distress at 12 cases (31.58%).And in cases of failure of immediate operative delivery (68%) of conventional signs of fetal distress, antenatal fetal death was registered within 2 days.In all cases of antenatal fetal distress in the first group of in the period at 26-32 weeks occurred the FGRS: the average fetal weight at birth was 1012 ± 157,63g and olygohydramnion (amniotic index was 4,6 ± 0,96sm).The zero and reverse diastolic component in the umbilical artery were first reported in term of 26 weeks in 33.3% of cases, in 27 weeks - 27.78%, at 29-30 weeks - 22.2%, to 32 weeks - 16 7%.At 2 ± 0,59 days to antenatal fetal death marked reversible α-wave (atrial contraction in phase) in the ductus venosusin the 88.89% cases, which reflects the development of critical heart failure due to intrauterine fetal hypoxia.The evaluation of reliability difference time limits identifying the critical flow in umbilical artery and ductus venosus fetal and using of calculation U-criterion Mann-Uinti (U-critical criterion 176,5≤ 17), found that the difference in terms of levels of signs to be compared statistically significant (p